Sport psychology concepts and applications - Cox, Richard H. (McGraw-Hill, 2012)
"Sport Psychology: Concepts and Applications shows how concepts supported by current scientific research can be used to address issues and situations encountered everyday by physical activity specialists, coaches, athletic trainers, and athletes. This introduction to sport and exercise psychology addresses practical issues, such as dealing with anxiety, arousal, and stress; developing coping, relaxation, motivation, and energizing strategies; understanding the effects of an audience on human performance; building team cohesion; and preventing burnout and other negative effects"--